Assessment of parents’ knowledge of space maintainers, in the western Black Sea region - Mihriban Gökcek Taraç (Current Research in Dental Sciences)
Objective: The increasing number of pediatric dentists in our country and their availability in state hospitals are effective in expanding preventive dentistry practices. However, the increasing incidence of caries and malocclusion shows that there is still a lack of information parents about preventive dental practices. In this study, it was planned to evaluate the parents’ knowledge of space maintainers in the western Black sea region of Turkey. Methods: In our study, intraoral examinations of Children who applying for dental treatment were performed, and dmft/DMFT values were noted. Parents were asked to complete a survey assessing their level of space maintainers knowledge, and the obtained data was analyzed.Results: A total of 412 parents and their Children participated in the study. According to the results, no significant relationship was found between the space maintainer knowledge levels of the parents and gender (p = 0.270), educational level (p = 0.298), and tooth brushing frequency (p = 0.810). The space maintainer knowledge levels of parents whose child previously had tooth extraction were found to be significantly higher (p=0.00). The mean dmft/DMFT of the patients was found to be 8.4. The relationship between dmft/DMFT values and knowledge levels was evaluated, and no significant relationship was found (p = 0.09).Conclusion: Early loss of primary teeth can lead to orthodontic problems if not treated properly. In order to prevent this situation, parents need to have information about maintaining oral and dental health and treating early tooth loss. Therefore, dentists should focus on preventive treatments rather than therapeutic approaches and inform parents very well.